What Role Does Medical Anthropology Play in Medical Education? A Scoping Review - Davide Costa; Raffaele Serra (Societies)
Background: The medical humanities (MH) are important in medical education, and one of the most relevant is medical anthropology. This discipline constitutes the bridge between the biomedical world and the human sciences because it can detect social, cultural, and psychological variables that can act as barriers to the provision of medical services in epidemic contexts, combining knowledge of pathologies in different cultures and epidemiology. Based on what has been reported so far, this article starts with a research question: what is the role of medical anthropology in medical education? Methods: A scoping review was established according to the PRISMAScR method to try to understand the role of this discipline in medical education. Results: In total, 22 articles were included, and the extracted data were organized into different themes: the reasons for teaching anthropology to medical students, methods used that are useful for medical students, teaching methods and techniques, and some problems regarding anthropology in medical education. Conclusions: The MH may support the decision-making of physicians, thus improving several physician skills to deliver the most appropriate care to patients. On the other hand, medical sciences may provide important feedback on medical anthropology to have an actual impact on curing and caring processes.